Method for fabricating microwave absorption ceramics with high thermal conductivity. Issue 2 (February 2018) - He, Yongqin; Li, Xiaoyun; Zhang, Jingxian; Li, Xiaoguang; Duan, Yusen; Huang, Mingming; Bai, Hainan; Jiang, Dongliang; Qiu, Tai
Abstract: In this work, a high-performance microwave absorption ceramic together with high thermal conductivity was proposed through the introduction of phenolic resin as the carbon source into AlN ceramic substrate. The phenolic resin was initially mixed with AlN powder and sintering additives in ethanol to form homogeneous slurries, followed by drying, pyrolysis, dry pressing and pressureless sintering to develop nano carbon in situ in AlN substrate. The well controlled microstructure with homogeneous distribution of nano sized carbon lead to the high thermal conductivity and excellent microwave absorption properties. by adjusting the phenolic resin content, the ceramic showed a minimal reflection coefficient of about −30 dB with an effective bandwidth of about 2 GHz together with a high thermal conductivity of about 135.1 W/m K.